Samuel Taylor Coleridge : the Highgate years, 1816-1834 - Kellaway, Michael (The University of Edinburgh, 1974)
This is a biographical thesis, describing Coleridge's life from 1816 to 1834, when he lived with the Gillmans at Highgate. Use has been made of unpublished material in the British Museum, the National Library of Scotland, and Dove Cottage Library, Grasmere, as well as manuscript letters in the possession of B.S. Frere.

The main themes are his insufficiently-determined attempts to break his addiction to laudanum, which ended in failure; his vain efforts to secure a pension or sinecure with the assistance of John Hookham Frere; his disappointment with his son, Hartley; his (usually bad) relationships with publishers; and his increasing disillusionment with the Magnum Opus and his own earlier philosophy.

Set against these disappointments were a new sense of peace and tranquillity from sharing the well-ordered life of the Gillmans; a growing reputation which brought him friends, "disciples" and many casual visitors, and which also made his family more appreciative of his worth; several important publications; and, after the crisis of 1810-1812, a movement towards a new, calmer relationship with Mrs Coleridge, the Wordsworths and Sara Hutchinson.